Pb, Cd, and As in soils and yerba mate branches from different cultivation areas - Martín, Cecilia Magalí (2023)
Yerba mate is cultivated in northeastern Argentina, southern Brazil, and southeastern Paraguay. Agricultural technology, industrial pollution, geological sources, and food processing are the most prominent sources of food contamination by toxic elements, including heavy metals.The objective of this work was to evaluate the influence of soil acidity and fertilization practices in Misiones on Pb, Cd, and As content in soil samples and yerba mate plantations. Chemical analyses were performed by ICP-MS, after microwave acid digestion.Determinations made according to soil acidity indicate that there are differences between areas and between plant fractions on Pb, and Cd content of plantations. Determinations made according to fertilization system, areas and level of fertilization do not have a significant effect on Pb, Cd, and As plantations content.Given that these elements are toxic and that maximum contents in yerba mate are regulated, it is important to study mitigation measures so that plants do not accumulate them in excess in their tissues.